2016
DOI: 10.2196/jmir.4767
|View full text |Cite
|
Sign up to set email alerts
|

Who Self-Weighs and What Do They Gain From It? A Retrospective Comparison Between Smart Scale Users and the General Population in England

Abstract: BackgroundDigital self-monitoring, particularly of weight, is increasingly prevalent. The associated data could be reused for clinical and research purposes.ObjectiveThe aim was to compare participants who use connected smart scale technologies with the general population and explore how use of smart scale technology affects, or is affected by, weight change.MethodsThis was a retrospective study comparing 2 databases: (1) the longitudinal height and weight measurement database of smart scale users and (2) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…Our findings are consistent with previous research showing that greater engagement with an intervention was associated with greater weight loss, even with different types of engagement measures [ 17 - 19 ]. For example, in a weight loss clinical trial testing the use of interactive voice response (IVR) technology for self-monitoring, 91 participants were randomized to either control or IVR for 12 months [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with previous research showing that greater engagement with an intervention was associated with greater weight loss, even with different types of engagement measures [ 17 - 19 ]. For example, in a weight loss clinical trial testing the use of interactive voice response (IVR) technology for self-monitoring, 91 participants were randomized to either control or IVR for 12 months [ 18 ].…”
Section: Discussionsupporting
confidence: 92%
“…detecting and reversing small regains) was explicitly stated either to participants or by participants . By contrast, ad libitum weighing in general population samples is unlikely to be naturally underpinned by this maintenance‐specific rationale and may thus be of lesser importance for maintenance in this context.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] For example, in a weight loss clinical trial testing the usage of interactive voice response (IVR) technology for self-monitoring, 91 participants were randomized to either control or IVR for 12 months. [17] Completion of the IVR calls was significantly correlated with weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Other research has also shown that weight loss was associated with greater engagement with participant self-weighing. [16,19,21, 22] A 6-month intervention showed that participants in the intervention group self-weighed more days/week (6.1 +/-1.1) than controls (1.1+/-1.5) and these participants lost significantly more weight than controls (-6.55% vs -0.35%).…”
Section: Discussionmentioning
confidence: 99%